Penataan Kawasan Wisata Torosiaje Serumpun di Kabupaten Pohuwato dengan Pendekatan Arsitektur Ekologi - Zulkifli Abdullah; Sri Sutarni Arifin; Muhammad Rijal Syukri (JAMBURA Journal of Architecture, 2021)
Ecotourism is an activity of environmentally friendly tourism by emphasizing aspects of nature conservation, empowerment of multiple factors (societal, economic, and cultural) as well as aspects of learning and education. Pohuwato is a regency in Gorontalo with such a diverse tourism type and possesses a huge potential in the tourism sector. Torosiaje cluster is one of the regions located in Popayato district, Pohuwato regency—a region that is now a tourist village. In addition to having maritime potentials, this area also has the mangrove potential spanning 7.420 Ha. The region experienced a decline in width due to land conversion by the public, which is now ponds as well as the source of firewood and building materials. The Village has ecological potentials and natural resources, but they are managed poorly. Thus, the development of an ecotourism site is required. Arranging the Tourist Area of Torosiaje cluster is the early stage to improve tourism necessities so that tourist accommodation for all tourist activities is needed.This research aims to design supporting facilities and infrastructure without damaging the environment based on the function of the mangrove ecotourism area. The application of the Ecological Architecture concept was devoted to the arrangement of the circulation area while maintaining and preserving the environment both in terms of the use of materials that do not damage nature and the proper use of energy based on the conservation area. Ecological architecture is a reciprocal relationship between living creatures and the environment. Keywords: Tourism Area, Mangrove Ecotourism, Ecological Architecture